(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This research focuses on describing the traditions of the prophet’s birthday in Demak regency. For the Demak community the festival traditions are different from other Muslim communities. Methodologically, this study uses a phenomenological approach by relying on participant-observation techniques and in-depth interviews. As for the results of this study, it can be concluded that the celebration of the Prophet’s birthday in the Demak community is carried out by reading poetic texts as contained in the books of al-Barzanji, al Dzibai and also Simth al Durar. Apart from that, there are food treats and meals, food distribution to neighbors and mayoran (eating together in one group). The reading of al Barzanji, al Dzibai, Simth al Durar is intended to understand the Sirah Nabawiyah (prophetic history) as an expression of the love for the prophet Muhammad and to do wasilah (intermediary prayer). In the activities of ater-ater and slametan it is intended to save oneself from all the troubles of life by means of alms